Efficacy of acupuncture treatment for breast cancer-related insomnia: study protocol for a multicenter randomized controlled trial - Yin, Ping; Fan, Qian; Liu, Lumin; Yang, Ming; Zhang, Shunxian; Li, Xu; Hou, Wenguang; Feng, Qifan; Wang, Xi; Jin, Zhu; Li, Fang; Chen, Yuelai (Frontiers in Psychiatry, 2024)
Background: Insomnia is one of the most common symptoms among breast cancer patients, which can be present throughout all stages of breast cancer. As a non-pharmacological alternative treatment, acupuncture has been suggested to improve sleep situations in patients with cancer suffering from insomnia. However, there is a lack of well-designed, high-quality clinical evidence regarding the efficacy of acupuncture in the treatment of breast cancer-related insomnia. This study is conducted to evaluate the efficacy and safety of acupuncture treatment for breast cancer-related insomnia.Methods: This study was designed as a multicenter, randomized, sham-controlled clinical trial. A total of 264 eligible patients with breast cancer-related insomnia will be randomized into an acupuncture group and a sham acupuncture group in a 1:1 ratio. In the trial, patients in the acupuncture and sham acupuncture groups will receive 12 sessions over a consecutive 4-week period. The primary outcome will be the treatment response rate of Insomnia Severity Index (ISI) at week 4; secondary outcomes include treatment remission rate of ISI, Sleep Efficiency (SE) obtained by the use of Sleep diary, treatment response rate of ISI at 8th and 16th weeks of follow-up, the mean changes of ISI, Generalized Anxiety Disorder Scale (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Quality of Life Questionnaire -Core 30 (QLQ-C30), sleep parameters recorded in Actigraphy and weekly usage of remedial drugs. Adverse events will be recorded throughout the study. All analyses will be based on the ITT principle and performed with SAS 9.4 statistical software.Discussion: This trial will evaluate the clinical efficacy and safety of acupuncture for breast cancerrelated insomnia. If proven effective, acupuncture will provide an effective option for patients with breast cancer-related insomnia, which will play a positive role in helping patients reduce their use of sleeping medications.Clinical trial registration: ClinicalTrials.gov, identifier NCT05510700.